Pregunta
upstudy study bank question image url

Solve for \( u \). \[ 3+\frac{1}{u+6}=-\frac{5}{(u+1)(u+6)} \] If there is more than one solution, separate them with If there is no solution, click on "No solution".

Ask by Long Macdonald. in the United States
Feb 27,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( u = -\frac{4}{3} \)

Solución

We are given the equation   3 + 1/(u + 6) = -5/[(u + 1)(u + 6)]. Step 1. Note the restrictions on u. Since u + 6 and u + 1 are in the denominators, we must have   u ≠ -6 and u ≠ -1. Step 2. Multiply both sides of the equation by (u + 1)(u + 6) to eliminate the fractions:   (u + 1)(u + 6)[3 + 1/(u + 6)] = (u + 1)(u + 6)[-5/((u + 1)(u + 6))]. This simplifies to:   3(u + 1)(u + 6) + (u + 1) = -5. Step 3. Factor out (u + 1) from the left-hand side:   (u + 1)[3(u + 6) + 1] = -5. Simplify inside the brackets:   3(u + 6) + 1 = 3u + 18 + 1 = 3u + 19. Thus, the equation becomes:   (u + 1)(3u + 19) = -5. Step 4. Expand the left-hand side:   3u² + 19u + 3u + 19 = 3u² + 22u + 19. Now set the equation equal to zero by adding 5 to both sides:   3u² + 22u + 19 + 5 = 3u² + 22u + 24 = 0. Step 5. Solve the quadratic equation:   3u² + 22u + 24 = 0. We use the quadratic formula, where a = 3, b = 22, and c = 24:   u = [ -22 ± √(22² - 4·3·24) ] / (2·3). Calculate the discriminant:   22² - 4·3·24 = 484 - 288 = 196. Since √196 = 14, we have:   u = [ -22 ± 14 ] / 6. This gives two possible solutions: • u = ( -22 + 14 ) / 6 = (-8)/6 = -4/3. • u = ( -22 - 14 ) / 6 = (-36)/6 = -6. Step 6. Check the solutions against the domain restrictions. Since u cannot equal -6 (because it makes the denominator u + 6 equal to zero), we must discard u = -6. Thus, the only valid solution is:   u = -4/3. Answer: -4/3

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve for \( u \) in the equation \[ 3+\frac{1}{u+6}=-\frac{5}{(u+1)(u+6)}, \] first, let's eliminate fractions by multiplying through by \((u+1)(u+6)\): \[ 3(u+1)(u+6) + (u+1) = -5. \] Expanding both sides: \[ 3(u^2 + 7u + 6) + u + 1 = -5. \] This simplifies to: \[ 3u^2 + 21u + 18 + u + 1 = -5. \] Combine like terms: \[ 3u^2 + 22u + 19 = -5. \] Now, add 5 to both sides: \[ 3u^2 + 22u + 24 = 0. \] Next, we can apply the quadratic formula where \( a = 3 \), \( b = 22 \), and \( c = 24 \): \[ u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{-22 \pm \sqrt{22^2 - 4 \cdot 3 \cdot 24}}{2 \cdot 3}. \] Calculating the discriminant: \[ 22^2 - 4 \cdot 3 \cdot 24 = 484 - 288 = 196. \] Since the discriminant is positive, we have two real solutions. Now plugging this back into the quadratic formula: \[ u = \frac{-22 \pm \sqrt{196}}{6} = \frac{-22 \pm 14}{6}. \] This gives us two possible values for \( u \): 1. \( u_1 = \frac{-22 + 14}{6} = \frac{-8}{6} = -\frac{4}{3} \), 2. \( u_2 = \frac{-22 - 14}{6} = \frac{-36}{6} = -6 \). Thus, the solutions for \( u \) are: \[ -\frac{4}{3}, -6. \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad